2011
DOI: 10.1073/pnas.1104954108
|View full text |Cite
|
Sign up to set email alerts
|

Long-term in vivo glucose monitoring using fluorescent hydrogel fibers

Abstract: The use of fluorescence-based sensors holds great promise for continuous glucose monitoring (CGM) in vivo, allowing wireless transdermal transmission and long-lasting functionality in vivo. The ability to monitor glucose concentrations in vivo over the long term enables the sensors to be implanted and replaced less often, thereby bringing CGM closer to practical implementation. However, the full potential of long-term in vivo glucose monitoring has yet to be realized because current fluorescence-based sensors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
233
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 284 publications
(237 citation statements)
references
References 27 publications
2
233
0
2
Order By: Relevance
“…The matrix of MNs was made from cross-linked HA to improve the stiffness of MNs and restrict the loss of GRVs from needles. With transcutaneous administration, the GRVs loaded in MNs disassembled when exposed to high interstitial fluid glucose in vascular and lymph capillary networks (35), thereby promoting the release of insulin, which was then taken up quickly through the regional lymph and capillary vessels (36). We demonstrated that this "smart insulin patch" with a novel glucoseresponsive mechanism displayed rapid responsiveness for glucose regulation and reliable avoidance of hypoglycemia in a mouse model of type 1 diabetes.…”
Section: Significancementioning
confidence: 92%
“…The matrix of MNs was made from cross-linked HA to improve the stiffness of MNs and restrict the loss of GRVs from needles. With transcutaneous administration, the GRVs loaded in MNs disassembled when exposed to high interstitial fluid glucose in vascular and lymph capillary networks (35), thereby promoting the release of insulin, which was then taken up quickly through the regional lymph and capillary vessels (36). We demonstrated that this "smart insulin patch" with a novel glucoseresponsive mechanism displayed rapid responsiveness for glucose regulation and reliable avoidance of hypoglycemia in a mouse model of type 1 diabetes.…”
Section: Significancementioning
confidence: 92%
“…[1b, 5] Optical sensors offer advantages over electrochemical assays since they can be constructed to be label-free, provide real-time continuous monitoring for long periods of time, are immune to electromagnetic interference, and can be calibrated internally. [6] One of the promising approaches for optical glucose sensors is to covalently incorporate glucose-sensitive chelating agents such as phenylboronic acid (PBA) derivatives [7] into matrixes such as or micro- and nanostructures including holographic thin films, [8] crystalline colloidal arrays, [9] plasmonic nanoantennas, [10] Fabry-Perot cavities, [11] fluorescent dyes, [12] and quantum dots (QDs). [13] Optical monitoring systems have also been developed in the form of solid-state optodes that report on the glucose concentration via refractive index (RI) changes.…”
mentioning
confidence: 99%
“…[19] For instance, optical polymer fibers based on fluorescent sensing have been reported for quantitative glucose measurements. [12] However, photobleaching of the fluorophore, and variations in the illumination source and output caused over/underestimation of the glucose concentration in vivo . Additionally, this technology was not applicable to individuals with skin pigmentation, light scattering from the tissue, and was affected by epidermal thickness.…”
mentioning
confidence: 99%
“…For high spatial resolution, these detectors require complex imaging modalities, such as two-photon confocal imaging, for reliable temporal and spatial resolution. Feasible use of such sensors in human patients will probably sacrifice spatial resolution for broad in vivo accuracy, as in embedded optical glucose sensors [4]. Positron emission tomography sensors are well established, with a growing list of increasingly validated substrates for in vivo sensing including glucose metabolism, oxygenation, neurotransmitters and proteases.…”
mentioning
confidence: 99%
“…Recent refinements of implantable optical detectors are a particularly promising development that will have major implications for the use of fluorescence-based biosensors [22]. These implantable optical sensors have recently been applied to great effect to subcutaneously assay glucose concentrations using a fluorescent hydrogel-based glucose sensor [4].…”
mentioning
confidence: 99%